2003
DOI: 10.1080/0269920031000111348
|View full text |Cite
|
Sign up to set email alerts
|

Phonological development: a normative study of British English‐speaking children

Abstract: This paper reports a normative study on the phonological development of British English-speaking children. Speech samples of 684 children, aged between 3;0 and 6;11 years, randomly selected from nurseries and schools in eight different areas throughout the UK, were collected and analysed to obtain normative data. This paper reports on two aspects of speech development: the age of acquisition of sounds (phonetic acquisition) and the age that error patterns were suppressed (phonemic acquisition). It discusses th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
318
7
31

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 322 publications
(396 citation statements)
references
References 3 publications
40
318
7
31
Order By: Relevance
“…Regarding the age of the participants, most of the sample consisted of children aged 5 years; they presented poorer results when compared to participants aged 4 years. This finding does not corroborate studies that show that the higher the age the better is the phonological suitability [17][18][19] . This research corroborates a national study that showed that children aged five years presented higher prevalence of phonological deviations when compared to the four years old group 20 .…”
Section: Resultscontrasting
confidence: 55%
“…Regarding the age of the participants, most of the sample consisted of children aged 5 years; they presented poorer results when compared to participants aged 4 years. This finding does not corroborate studies that show that the higher the age the better is the phonological suitability [17][18][19] . This research corroborates a national study that showed that children aged five years presented higher prevalence of phonological deviations when compared to the four years old group 20 .…”
Section: Resultscontrasting
confidence: 55%
“…The scale contains only one set of levels; no age bands have been created. However, it is acknowledged that at four years children's phonological system, and potentially their intelligibility, will still be developing (Dodd, Holm, Hua, & Crosbie, 2003) and in the introduction to the scale examples of developmental speech substitutions are given. The scale may be easier to apply with older children, whose speech has matured.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst a definitive cut off age for the definition of PSD has not been agreed, it has generally been applied to children of approximately age 8 and above. This is logical given that speech acquisition is generally considered to be complete by this age (Dodd, Holm, Hua & Crosbie, 2003;James, 2001;Smit, 1993aSmit, , 1993b. Moreover, Shriberg, Fourakis, Hall, Karlsson, Lohmeier, McSweeny et al (2010) justify a cut off between age 8 and 9 on the basis that children whose speech disorder continues beyond this age are small in number but more at risk for long term persistence and associated sequelae, sometimes into adulthood.…”
Section: Introductionmentioning
confidence: 99%